An Analysis Of Studentsâ Writing Skill in Narrative Text at The Second Grade Studentsâ at SMAN 3 Rambah Hilir - Noviani, Almia; Donal, Andri; Rasyidah, Ummi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research was to know the skill of the second grade students of SMAN 3 Rambah Hilir of in writing narrative text. The sample of this research were second grade students of SMAN 3 Rambah Hilir Kabupaten Rokan Hulu. The class consists, of 21 students; the researcher used total sampling technique to determine the sample research. The research was descriptive qualitative .The purpose of this research was to described the situation objectively. This research was done with some steps. They were collecting the data, analyzing the data, making conclusions, and reporting result. The result of research showed that the skill of second grade students of SMAN 3 Rambah Hilir in Poor category was 0%, in good category was47, 61%. In excellent category were 19, 04 %. Then, in fair category was 28,57%, in very poor category was 4,76%. The average score was 74, 19 %. So, it can be concluded that the students writing skill in narrative text at second grade of SMAN 3 Rambah Hilir was good.